'The voice of an oracle': Little Nell and the art of 'enacting the persona of the doctor'. Issue 12 (December 2022) - Cooper, Maxwell
Medical humanities have long been promoted as a means for trainees and doctors to gain deeper understanding of patients, illness and professionalism. In practice, teaching on medical humanities – while valuable –struggles to connect such learning to the realities of the clinical workplace and patient encounters. The solution to this shortcoming lies in recognising 'soft', but clinically relevant, concepts that operate within consultations. These concepts are, in fact, best revealed through literary and historic accounts of doctors, patients and illness. Such a vignette is Dickens' parody of Victorian physicians in the shape of the doctor who visits Little Nell in his book the Old Curiosity Shop . By taking prescription and technology out of the encounter, Dicken's parody lays bare 'soft' elements that constitute the art of 'enacting the persona of the doctor'. Medical humanities in general (and literature in particular) constitute a valuable tool for teaching the place of performance and the power of human qualities in the consultation. This 'old fashioned' professionalism should be a foundation to every formation in clinical medicine.